Field and modeling studies of aquifer heterogeneity to improve remediation planning in a multilayered aquifer system - Gigliuto, Andrea; Righetti, Chiara; Vaccari, Roberta; Moretti, Leandro (Acque Sotterranee - Italian Journal of Groundwater, 2012)
This paper presents the work carried out at a coastal contaminated site to define the presence and nature of heterogeneities in a complex hydrogeological aquifer system. The aim of the studies was to identify the effects of acquifer heterogeneities affecting plume migration in order to support remediation strategies. The hydrogeology of the area is characterized by the presence of a multilayer aquifer and a close relationship between groundwater and surface water (tidal fluctuations, lake system). Different approaches were utilized to investigate the system, including field and modeling studies. Field investigations included continuous groundwater level monitoring system, the monitoring of multi-level wells and the installation and sampling of new monitoring wells in order to define the vertical distribution of the chlorinated solvents (CAHs) contamination. The complexity of the hydrogeological system required hydraulic tests and tracers tests in order to verify the hydraulic interactions between aquifer layers and their relationship with surface water. The modeling studies have included the implementation of 3 separate numerical models of groundwater flow, aiming to verify the effectiveness of the previous site emergency remedial actions and to support remediation strategies in different project phases. The studies allowed to understand the downward plume migration of the CAHs: vertical hydraulic gradients induced by the surface water system and the complexity of the multilayered aquifer system due to presence of heterogeneities mainly affected the CAHs transport in the first acquifer.